2017
DOI: 10.1074/jbc.m117.787622
|View full text |Cite
|
Sign up to set email alerts
|

Domain alternation and active site remodeling are conserved structural features of ubiquitin E1

Abstract: E1 enzymes for ubiquitin (Ub) and Ub-like modifiers (Ubls) harbor two catalytic activities that are required for Ub/Ubl activation: adenylation and thioester bond formation. Structural studies of the E1 for the Ubl mallbiquitin-like difier (SUMO) revealed a single active site that is transformed by a conformational switch that toggles its competency for catalysis of these two distinct chemical reactions. Although the mechanisms of adenylation and thioester bond formation revealed by SUMO E1 structures are thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Interestingly, HS4 was partially occupied by the Uba1 inhibitor NSC624206 in a recently determined crystal structure of S. pombe Uba1 (PDB code 5UM6) ( Fig. 7B) (22), and although this interaction was not involved in the inhibitory mechanism of the molecule, it further validates the results of the FTMap analysis. Targeting HS1 and HS2 could be a way to perturb the adenylation and E2-binding activity of hUba1, and with the rapid development of protein-targeting chimeric molecule approaches (33) even HS3 and HS4, which would not appear to have an obvious functional consequence of small molecule binding, could potentially be co-opted for proteolytic targeting of hUba1.…”
Section: Computational Analysis Of Ligand-binding Hot Spots On Human supporting
confidence: 76%
See 3 more Smart Citations
“…Interestingly, HS4 was partially occupied by the Uba1 inhibitor NSC624206 in a recently determined crystal structure of S. pombe Uba1 (PDB code 5UM6) ( Fig. 7B) (22), and although this interaction was not involved in the inhibitory mechanism of the molecule, it further validates the results of the FTMap analysis. Targeting HS1 and HS2 could be a way to perturb the adenylation and E2-binding activity of hUba1, and with the rapid development of protein-targeting chimeric molecule approaches (33) even HS3 and HS4, which would not appear to have an obvious functional consequence of small molecule binding, could potentially be co-opted for proteolytic targeting of hUba1.…”
Section: Computational Analysis Of Ligand-binding Hot Spots On Human supporting
confidence: 76%
“…Studies of the E1 for the Ub-like modifier SUMO have shown that the thioester bond formation involves disassembly of the adenylation active site and an ϳ130°rotation of the SCCH domain that transits the catalytic cysteine and other structural elements required for catalysis of thioester bond formation into the active site (24,25). A similar SCCH domain rotation of ϳ106°w as observed for the S. pombe ortholog of Uba1 (22). Finally, the ubiquitin fold domain, UFD, recruits E2 enzymes in a "distal" conformation and subsequently rotates to a more "proximal" conformation that places the E1 and E2 catalytic cysteines into proximity to facilitate E1-E2 thioester transfer (19).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Disassembly of the adenylation active site and concomitant assembly of the thioester bond formation active site following SUMO adenylation and pyrophosphate release serves as a mechanism to drive the SUMO activation process forward 27 . It is likely that other Ubl E1s undergo similar conformational changes during the course of their catalytic cycles 13 , 27 , 40 .…”
Section: Introductionmentioning
confidence: 99%